2018
DOI: 10.3390/brainsci8120219
|View full text |Cite
|
Sign up to set email alerts
|

Facial Sadness Recognition is Modulated by Estrogen Receptor Gene Polymorphisms in Healthy Females

Abstract: Polymorphisms of the estrogen receptor ESR1 and ESR2 genes have been linked with cognitive deficits and affective disorders. The effects of these genetic variants on emotional processing in females with low estrogen levels are not well known. The aim was to explore the impact of the ESR1 and ESR2 genes on the responses to the facial emotion recognition task in females. Postmenopausal healthy female volunteers were genotyped for the polymorphisms Xbal and PvuII of ESR1 and the polymorphism rs1256030 of ESR2. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 126 publications
(153 reference statements)
0
1
0
Order By: Relevance
“…The cellular effects of estrogen are mediated by two estrogen receptors (ERα, ERβ), which regulate the physiological processes such as cell growth and development, and closely related to the pathological processes such as inflammation, osteoporosis, cancer, and neurodegeneration ( Jia et al, 2015 ). ERα has significant effects on mood and cognition, and variants in estrogen receptors may alter estrogen signaling and increase susceptibility to depression, anxiety in women ( Gutiérrez-Muñoz et al, 2018 ). Previous evidences showed that specific ESR1 polymorphisms might contribute to the increased susceptibility to the development of anxiety disorders ( Borrow et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The cellular effects of estrogen are mediated by two estrogen receptors (ERα, ERβ), which regulate the physiological processes such as cell growth and development, and closely related to the pathological processes such as inflammation, osteoporosis, cancer, and neurodegeneration ( Jia et al, 2015 ). ERα has significant effects on mood and cognition, and variants in estrogen receptors may alter estrogen signaling and increase susceptibility to depression, anxiety in women ( Gutiérrez-Muñoz et al, 2018 ). Previous evidences showed that specific ESR1 polymorphisms might contribute to the increased susceptibility to the development of anxiety disorders ( Borrow et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%